THE CONSEQUENCES OF STUDENTS’ EATING BEHAVIORS AND FOOD PERCEPTION ON THEIR NUTRITIONAL STATUS AND ACADEMIC ACHIEVEMENT - Teves, Karen Luz; Narciso, Joseph Faith (PEOPLE: International Journal of Social Sciences, 2017)
Maximization of growth and learning among students requires the support of good nutrition. Students’ food perception affects their food selection decision which in turn influences their nutritional status and academic performance. Generally, students choose food to eat based on taste, cost, nutritional benefits, convenience and pleasure, among others. As they grow up and leave their family to attend higher studies, it is a critical period for them because they make their own food decisions that can impact eating behaviors. In this study, the respondents were 348 Secondary from the six schools of DepEd Mabinay District II, Mabinay, Negros Oriental, Philippines. Factors such as students’ socio-demographic profile, extent of eating behavior, perceptions on healthy food, academic performance and nutritional status were looked into and inter-relationship of these variables was investigated. Results showed that majority of the respondents aged 13-16 years old, female, have daily allowance of PhP20 and whose parents have meagre monthly income of PhP3000 and below. On extent of eating behaviour, students ate/drink bread, pastries, junk foods, candies and soft drinks. They general choose food to eat based on taste. In terms of academic achievement, majority were average students and when it comes to nutritional status, majority were normal, very few were underweight and obese.under eating. No significant relationship was found between students’ profile and their perception of healthy foods and also with their eating behaviour and food perception. A strong significant positive correlation was found between students’ eating behaviour and nutritional status but there was no significant relationship between the respondents’ nutritional status and academic performance. Though academic performance was not influenced by students’ eating behaviour and food perception, the Department of Education in the country should closely check students’ frequency of eating junk food as it pose ill effects on their health.